2015
DOI: 10.1007/s10815-015-0577-0
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of an age-related correlation of ovarian reserve and FMR1 repeat number among women with “normal” CGG repeat status

Abstract: Purpose The objective of this analysis is to examine the relationship between Fragile X Mental Retardation 1 gene (FMR1) cytosine-guanine-guanine (CGG) repeat number and ovarian reserve, with a particular focus exclusively on the range of CGG repeat number below the premutation (PM) range (<55 CGG repeats). Methods Our study included female patients who underwent assessment of FMR1 CGG repeat number and serum antiMullerian hormone (AMH) in 2009-2014. To examine the association between FMR1 repeat number and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…With intermediate (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and premutation carriers (55-200 CGG repeats), we notice a translation fault which can be held accountable for mRNA production levels [93] not balanced through an equivalent rise in FMRP that frequently is normal or somewhat reduced. By consequence, the mRNA levels build-up in the cells where it is hypothesized to exert cytotoxic effects (RNA/protein toxic gain-of-function disorder).…”
Section: How Fmr1 Mutations Influence Different Phenotypesmentioning
confidence: 83%
See 2 more Smart Citations
“…With intermediate (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and premutation carriers (55-200 CGG repeats), we notice a translation fault which can be held accountable for mRNA production levels [93] not balanced through an equivalent rise in FMRP that frequently is normal or somewhat reduced. By consequence, the mRNA levels build-up in the cells where it is hypothesized to exert cytotoxic effects (RNA/protein toxic gain-of-function disorder).…”
Section: How Fmr1 Mutations Influence Different Phenotypesmentioning
confidence: 83%
“…This 'normal' range, however, may not in fact be a homogenous population. Gleicher et al reported the intermediate genotype (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) repeats) expresses a minor instability unrelated to a definite phenotype or to the fragile X syndrome (FXS) within one generation, even though the risk is consistent in two generations [113]. These intermediate carriers, compared to 'normal', show a greater prevalence of subfertility, menstrual cycle anomalies, overall earlier than anticipated menopause (by ∼7 years), premature ovarian failure (32 vs 1 %), increased prevalence of osteoporosis, higher rate of aneuploidy, miscarriage and even perhaps non-identical twinning rates [85,94].…”
Section: The Cgg Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we did not have activation ratio data, one X chromosome was selected for analysis in the present study as follows. Although we considered alternative approaches [Kline et al, 2014; Gustin et al, 2015], we followed the approach of Hunter et al [2012]. We selected the longer allele in mothers who had one expanded (i.e., > 40 CGGs) allele and one normal allele (n = 218) and in the one case who had two expanded alleles.…”
Section: Methodsmentioning
confidence: 99%
“…These findings have prompted some investigators to questions if the true normal range of CGG repeats should be narrowed to 26-34 repeats (Gleicher et al, 2014). These suggestions, however, remain controversial, as other studies have either failed to demonstrate that variation in the normal CGG repeat range is associated with markers of ovarian reserve (Schufreider et al, 2015) or suggested that the effect of CGG repeat number is modified by the patient's age (Gustin et al, 2015;Pastore et al, 2014). Therefore, no consensus has been reached on whether CGG repeat number in the normal range affects ovarian reserve or whether this effect is only present in a subset of the infertile population.…”
Section: Introductionmentioning
confidence: 99%